Inggris Sebagai Sentral Keuangan Islam di Barat - Irvani, Ahmad (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2016)
United Kingdom is a country that is predominantly by non-Muslim, but development of Islamic banking and finance is very good. This is evidenced by the operation of six full sharia bank and the sixteen banks that serve Islamic windows. Sukuk deals for investors is also growing as evidenced by the increasing demand on the London Stock Exchenge with a total of £51 billion. Likewise with takaful products, UK re/insurance markets that are transacting Islamic finance. As one of the largest insurance markets in the world, and the leading global centre for wholesale insurance and reinsurance, the UK has the potential to support the growth of takaful business in the coming years. The development of Islamic banking and finance did not escape from the multicultural population of the UK. From the research, UK residents both Muslims and non-Muslims showed 66% of respondents believe the Islamic financial system is suitable for western economic communities such as the UK. 65% of respondents understand the workings of Islamic banking differs from conventional banking workings. 60% of respondents agree Islamic banking relevant to all religions. 57% of respondents also knew of Islamic banking to give the profit, not the interest. This means that they responded positively to the products offered Islamic banking and finance. There are several factors that lead to Islamic banking and finance can be grown in the UK, there are: including the global expansion of Islamic financial, single banking and financial regulator, public policy and taxation, the establishment of the Islamic Bank of Britain, the excess liquidity in the Middle East, Islamic windows of regular banks, and the development of educational and training institutions in the UK. This paper will describe the history of Islamic banking and finance in the UK, its development, factors that support and the its future prospects for giving additional knowledge to the academics and practitioners.